Cloning and temperature-dependent expression in Escherichia coli of a Legionella pneumophila gene coding for a genus-common 60-kilodalton antigen. - Hoffman, P. S. (1989)
All Legionella species express a 60-kilodalton (kDa) protein which contains a genus-specific epitope recognized by murine monoclonal antibody GW2X4B8B2H6. A genomic cosmid library of Legionella pneumophila chromosomal DNA was constructed in pHC79 and screened for 60-kDa antigen-expressing clones with the monoclonal antibody. A 3.2-kilobase EcoRI fragment from cosmid 14B11 expressing a 60-kDa protein was subcloned into pUC19 (pSH16), and deletion of a 1.2-kilobase HindIII fragment (pSH16A) generated a 33-kDa truncated polypeptide no longer reactive with the monoclonal antibody. Southern blot analysis of chromosomal DNA from selected Legionella species restricted with EcoRI and probed with the 1.2-kilobase fragment coding for the carboxyl region of the protein revealed DNA homology which was not observed with DNA from Escherichia coli. Maxicell analysis of pSH16 identified a second polypeptide of approximately 15 kDa expressed from a gene (htpA) upstream of the gene coding the 60-kDa protein (htpB). Both proteins were preferentially synthesized by L. pneumophila following heat shock (temperature shift from 25 to 42 degrees C), and under steady-state growth conditions the relative level of 60-kDa protein was unaffected by temperature. In E. coli, expression of a 60-kDa protein from pSH16 also increased following heat shock (25 to 42 degrees C), but under steady-state conditions expression was temperature dependent. Temperature-dependent expression from pSH16 was not observed in an rpoH (htpR) mutant strain of E. coli. The Legionella 60-kDa protein appears to be a heat shock protein which shares cross-reactive epitopes with the GroEL homolog of E. coli. In addition, a region of htpB encoding the 27-kDa carboxyl portion of the protein containing the monoclonal antibody-reactive epitope also contains DNA sequences unique to and conserved within the genus.